Secondary pulmonary alveolar proteinosis treated by lung transplant: A case report - David Lawi; Estelle Dubruc; Michel Gonzalez; John-David Aubert; Paola M. Soccal; Jean-Paul Janssens (Respiratory Medicine Case Reports, 2020)
Background.Pulmonary alveolar proteinosis (PAP) is a pulmonary disease characterized by disruption of surfactant homeostasis resulting in its accumulation in the alveoli. PAP is classically classified into three categories (Table 1): 1/primary (or autoimmune) with antibodies targeting the GM-CSF pathway, 2/secondary to another disease, typically a hematologic malignancy, and 3/genetic.Case-report.A 30 year-old woman received an allogenic hematopoietic stem cell transplantation (HSCT) after treatment for acute myeloid leukemia (AML). Within the first 6 months post HSCT, she developed an ocular, oral, digestive and hepatic graft-versus-host disease associated with a mixed ventilatory defect with a very severe obstructive syndrome and a severe CO diffusion impairment. High resolution computed tomography showed a classical “crazy paving” pattern. Aspect and differential cell count of BAL were normal. All microbiological samples remained culture negative. Histo-pathological analysis of transbronchial biopsies was unremarkable. Because of the severity of the respiratory insufficiency, open-lung biopsy (OBL) could not be performed. Despite multiple immunosuppressive therapies, lung function deteriorated rapidly; the patient also developed an excavated fungal lesion unresponsive to treatment. She underwent a bilateral lung transplant 48 months after HSCT. Histo-pathological analysis of explanted lungs showed obliterative bronchiolitis (OB), diffuse PAP and invasive cavitary pulmonary aspergillosis.Conclusions.This case illustrates the simultaneous occurrence of OB, PAP and a fungal infection in a 30-year old female patient who underwent HSCT for acute myeloid leukemia (AML). To our knowledge this is the only documented case of PAP associated with OB treated by lung transplantation.